Policy Analysis of the Merdeka Curriculum in Enhancing Learning Quality: A Systematic Literature Review - Sabrina Arfa Andani; Eddy Haryanto; Masbirorotni Masbirorotni (Journal of Educational Sciences, 2026)
This study is motivated by the need to strengthen educational policy in Indonesia to address 21st century learning challenges, particularly in improving learning quality through the implementation of the Merdeka Curriculum. The study aims to analyze the effectiveness of the Merdeka Curriculum policy in enhancing learning quality. This research employs a systematic literature review (SLR) approach based on PRISMA guidelines, involving the identification, screening, and analysis of relevant scholarly articles from Google Scholar, Scopus, and Science Direct published between 2014 and 2024. The findings indicate that the implementation of the Merdeka Curriculum positively contributes to learning quality by increasing student engagement, promoting flexible learning, and developing 21st century competencies such as critical thinking, creativity, communication, and collaboration. However, several challenges remain, including limited teacher understanding, inadequate infrastructure, and uneven implementation across regions. In conclusion, the Merdeka Curriculum has strong potential to improve learning quality, but its effectiveness depends on continuous support through teacher professional development, adequate facilities, and adaptive policy evaluation.